Does The Smart Tourism Experience in Malaysia Increase Local Tourists’ Happiness and Revisit Intentions? - Ruslan, Noraini; Ying, Khoo Pei; Abu Hassan, Fasihah; Abdul Halim, Abdul Muhaimin; Arba’ain, Anes Farhanna; Muazam, Fatin Nur Izzati; Rashidi, Intan Farah Farina; Valerience, Ng Wei Inn; Mohamed Zamri, Nur Fatini; Zol, Nurul Uzzaty; Jasni, Jannatulhawa (Journal of Sustainable Natural Resources, 2023)
Nowadays, the term "smart" has become popular in reflecting technological advancements in social and economic improvement, as well as knowledge and information exchange. The advent of smart technology has empowered everything to be more connected, informed, and conveniently involved with clients, especially in the global tourism industry. Malaysia, on the other hand, has less research on the use of smart tourism since it is still in the early stages of development, and tourism locations are still seeking their own rhythm to thrive. In addition, there is a lack of a specific framework, numerous global-scale crises with negative impacts on tourist arrivals and the environment, and poor digitalization, which has resulted in a drop-off in tourist experiences and tourism development. This study was carried out to investigate whether local tourists are satisfied with the smart tourism technology experience in Malaysia and to explore whether smart tourism technology has a positive effect on tourists’ happiness. An online questionnaire was created using Google Form, distributed through WhatsApp, Telegram, Facebook, Instagram from May 1, 2021, to August 1, 2021, and completed by 529 participants. The results suggested the majority (> 90%) of local tourists in Malaysia found difficulty searching for information about the local attractions in each state of Malaysia during travel, which caused a greater decline in their excitement to do local traveling. With reliable centralized mobile apps that exist for all tourism sectors in Malaysia, research finding showed that it could increase tourist’s revisit intention and happiness, which consequently boosts the revenue of the economy.